The Influence Of The Work Environment And Work Discipline On The Work Productivity Of Althaf Kawalu Tasikmalaya Convection Employees: - Pirena, Demas; Karmila, Mila; Wibawa, Gian Riksa (Journal of Management, Economic, and Accounting, 2024)
This research aims to determine the influence of the work environment and work discipline on employee work productivity at the Althaf Kawalu Tasikmalaya convection. The method used in this research is a quantitative approach with an assessment sample of 40 respondents from Althaf Kawalu Tasikmalaya employees. The data used in this research is primary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the research results, it can be concluded that simultaneously the work environment and work discipline have a significant effect on employee work productivity at the Althaff Kawalu Tasikmalaya convection. Likewise, the work environment partially has a significant effect on employee work productivity. partially, work discipline has a significant effect on the work productivity of Althaf Kawalu Tasikmalaya convection employees.